Microbial degradation of dyes: An overview - Varjani, Sunita; Rakholiya, Parita; Ng, How Yong; You, Siming; Teixeira, Jose A. (Bioresource technology, 2020)
[Display omitted] •Technologies used for degradation of dyes have been reviewed.•Integration of technologies is important for remediation of pollutants.•Microbial degradation is environment friendly technique to control pollution.•In depth studies are necessary to close knowledge gaps in field of biodegradation. Industrialization increases use of dyes due to its high demand in paper, cosmetic, textile, leather and food industries. This in turn would increase wastewater generation from dye industrial activities. Various dyes and its structural compounds present in dye industrial wastewater have harmful effects on plants, animals and humans. Synthetic dyes are more resistant than natural dyes to physical and chemical methods for remediation which makes them more difficult to get decolorize. Microbial degradation has been researched and reviewed largely for quicker dye degradation. Genetically engineered microorganisms (GEMs) play important role in achieving complete dye degradation. This paper provides scientific and technical information about dyes & dye intermediates and biodegradation of azo dye. It also compiles information about factors affecting dye(s) biodegradation, role of genetically modified organisms (GMOs) in process of dye(s) degradation and perspectives in this field of research.